The Therapeutic Role of Ruqyah Syar’iyyah in Addressing Non-Medical Health Issues - Faiz, Muhammad (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the function, characteristics, and correct methods of Ruqyah Syar’iyyah in addressing non-medical illnesses, with a focus on its relevance to contemporary mental health challenges. Methodology: Using a qualitative approach, this research applies library-based analysis, drawing on classical Islamic texts, contemporary scholarly works, and relevant empirical studies. Sources were selected based on thematic relevance, credibility, and alignment with Islamic principles. Thematic analysis was conducted to identify core functions, procedural characteristics, and ethical guidelines of Ruqyah Syar’iyyah. Main Findings: Findings indicate that Ruqyah Syar’iyyah serves dual roles as therapeutic and preventive therapy for physical, psychological, and spiritual ailments. When combined with complementary practices such as cupping or herbal remedies, it shows increased efficacy. The practice emphasizes spiritual integrity, adherence to Islamic law, and active patient engagement. Novelty/Originality of this study: This research provides a structured framework linking Ruqyah Syar’iyyah with modern mental health discourse, highlighting its potential as a culturally grounded, faith-based therapeutic approach. It also offers an operational guideline for practitioners based on Qur’anic and Prophetic traditions.